Rancangan Monitoring Wind Direction Indicator Berbasis Arduino di Bandar Udara Indonesia - Rossydi, Ahmad; Yuyun Irmayanti, Andi; Sugiyanto (Politeknik Penerbangan Makassar, 2021)
Windsock is a marker of wind and relative wind speed. This tool is very useful in the world of aviation. Every airport must have a windsock as a support for determining the direction of the wind. This tool is installed at an airport that can be seen clearly by air traffic officers (ATC). But at the airport, A.P.T. Pranoto-Samarinda still uses a manual system to view the windsock using long-distance binoculars. The background of the development of this tool is due to the lack of effectiveness and efficiency when using the windsock which is already available at A.P.T Airport. Pranoto Samarinda. So here the author is interested in raising a title in this final project, namely